Perception of vocal difficulties in people with Parkinson's disease: a perspective from the socio-family environment. (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2023)
Introduction: Parkinson's disease (PD) is a complex neurodegenerative process that occurs in adulthood and can cause motor and non-motor symptoms. The voice of people with PD changes, which can affect their communication with their environment, as it also changes how others perceive their voice. Objective: To assess the perception of vocal difficulties in people with PD from the perspective of their social and family environment. Methodology: A cross-sectional, descriptive, observational study was conducted with the participation of 17 family members of members of the Association of People with Parkinson's Disease, family members, and friends from the city of Temuco (primary caregiver of the person with PD). Sampling was carried out using a face-to-face survey adapted from the VHI-30. Results: 71.2% of participants were over 40 years old, 76.5% were women, and they spent more than 5 hours a day with their family member with PD. 76.4% of participants perceived some impact of vocal difficulties on their family member with PD, considering functional, physical, and emotional criteria. Of these, 29.4% had mild to moderate difficulties, and 47% had severe to severe difficulties. Conclusion: Family members and/or caregivers may perceive vocal difficulties in people with PD to varying degrees. Involving the community and family during therapeutic support is essential for coping with the disease.
Keywords: Parkinson's disease; voice disorders; speech; family